Analisis Corporate Social Responsibility dan Kepemilikan Manajerial Terhadap Nilai Perusahaan Pada Sektor Pertambangan Di Bursa Efek Indonesia Periode 2014-2018 - Median Wilestari; Rini Putri Handayani (AKRUAL : Jurnal Akuntansi dan Keuangan, 2019)
This research aims to determine the effect of Corporate Social Responsibility and Management Ownership on company value. Sample of this research used mining company listed on the Indonesia Stock Exchange (IDX) and published an annual report in 2014-2018. The dependent variable in this research is the company value by Price to Book Value (PBV). The independent variables in this research are Corporate Social Responsibility disclosure index.and Managemen Ownership which is proxied by the Propotion of shared owned by the company. The measurement of the Corporate Social Responsibility disclosure index refers to the preservation report of Global Reporting Index version 4 (GRI4). The result show Corporate Social Responsibility has a no significant positif effect oncompany., but the management ownership has a significant negatif on Compant Value.. The coefficient of determination (R2) is 88% compared to the independent variable (X) on the variable Company Value (Y) in 2014-2018. While 12% is contributed by other factors